Politics and change in developing countries : tudies in the theory and practice development / edited by Colin Leys - "Leys, Colin. (ed.)" (Cambridge, 1969)
On 25 October 1968, Peter Nettl was killed in a plane crash in the U.S.A. To those who had the good fortune to work with him the loss of this brilliant and warm-hearted colleague, at the height of his powers, was a heavy personal blow. We would like this book, to which he contributed much more than his own paper, to be in some measure a tribute to him.
Keywords: Ideology